Is there evidence for using anticonvulsants in the prevention and/or treatment of delirium among older adults?. (24th March 2021) - Gupta, Aarti; Joshi, Pallavi; Bhattacharya, Gargi; Lehman, Melissa; Funaro, Melissa; Tampi, Deena J.; Tampi, Rajesh R.
ABSTRACT: Objective: This systematic review aims to identify published randomized controlled trials (RCTs) that evaluated the use of anticonvulsants for the prevention and/or treatment of delirium among older adults. Methods: A comprehensive search of databases: MEDLINE ALL (Ovid), Embase (Ovid), PsycINFO (Ovid), Web of Science Core Collection and Cochrane Central Register of Controlled was conducted. Results: The search identified four RCTs that evaluated the use of anticonvulsants among older adults with delirium. One RCT evaluated the perioperative use of gabapentin among individuals undergoing spinal surgery and the development of postoperative delirium. One RCT evaluated the relationship between the use of perioperative gabapentin and the development of postoperative delirium among individuals undergoing spinal surgery and hip and knee arthroplasty. Two post-hoc analyses of RCTs evaluated the use of gabapentin and pregabalin among individuals undergoing total knee arthroplasty (TKA) and total hip arthroplasty (THA). The perioperative use of gabapentin reduced the incidence of postoperative delirium among older adults undergoing spinal surgery. The perioperative use of gabapentin did not reduce the rates, severity or duration of postoperative delirium among older adults who were undergoing spine and hip and knee arthroplasty. The perioperative use of gabapentin did not reduce the incidence or duration of postoperative delirium among older adults undergoing elective TKA. The perioperative use of pregabalin did not reduce the incidence of postoperative delirium among older adults undergoing elective THA. Gabapentin and pregabalin were well tolerated among the individuals enrolled in these trials. There were no RCTs identified that evaluated the use of other anticonvulsants for the prevention and/or treatment of delirium among older adults. Conclusions: Based on current evidence, the routine use of anticonvulsants for the prevention and/or treatment of delirium among older adults cannot be recommended.